The nutritional ecology of the ant, Pheidole ceres - Judd, Timothy M., author; Herbers, Joan M., advisor; Moore, Janice, committee member; Baker, Myron, committee member; Alexander, Richard, committee member; Breed, Michael, committee member; Bjostad, L. B., committee member (Colorado State University. Libraries, 2003)
I examined the nutritional ecology of the ant Pheidole ceres, a small ant living in the Rocky Mountains, where the seasons range from hot summers to cold winters. If colonies behave the same as solitary organisms, then in this climate, one should expect 1) colonies P. ceres to reproduce during warmer months when food is abundant and store food when the colder months approach to prepare for times when food is absent. 2) The colonies should change their nutritional intake to match their strategy. While reproducing, animals take in more protein and when preparing for winter, change their dietary intake to high-energy foods. Field colonies presented with a choice between protein and carbohydrate sources foraged for both nutrients equally in the spring. At this time, the colony was rearing worker and reproductive destined larvae. In mid-summer, when adult reproductives were present, colonies preferred carbohydrates. This preference was maintained in the fall, when there were only worker-destined larvae. Thus, P. ceres colonies showed the greatest preference for protein when the colony was reproducing. This preference changed to carbohydrates as they fattened up their reproductives and prepared for the upcoming winter. One possible mechanism that would have produced this change in diet was workers were cuing in on the needs of the larvae. To test this, I created colonies consisting of brood deprived of one nutrient and workers deprived of another. The workers ignored needs of the larvae and responded only to their own needs. Thus, larvae have no influence over worker foraging behavior in P. ceres. P. ceres stores food internally as well as in seeds they collect. I analyzed individual ants and seeds, collected monthly, for the amount of protein, free amino acids, carbohydrates, and lipids. Lipids and proteins showed very little fluctuation over the year. However, the seeds contained lipids and protein, suggesting seeds are the primary source for these nutrients. Amino acids and carbohydrate levels correlated with the ants' foraging preference for protein and carbohydrates intake respectively. These results suggest that P. ceres workers are possibly cuing in on their own stores when making foraging decisions.
Keywords: zoology; entomology; ecology